Strengthening Village Accountability Through Socialization and Community Participation in the Concept of Good Governance - Maria Helena Kono Naiobe; S. Miranda, Natalisio; S.T Ati, Romario Finsensius; Tatu Sius, Karolus; Palan Peten, Yasinta (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
An understanding of government as an ever-changing organization must be able to be adapted to certain situations. This is why the idea of good governance is the basis for the government to do its best for the whole of society. socialization about realizing village accountability in the concept of good governance in the form of delivering material carried out by students of Widya Mandira Kupang Catholic University. interviews with the Ngegedhawe Village government regarding activities that will be carried out later. interviews through a question and answer process for implementing socialization activities where the aim of holding this socialization is to be an activity that reminds the Village government to realize village accountability in the concept of good governance resulting in increased understanding regarding the principles of good governance, especially accountability, transparency and participation, the importance of usingnv Village Funds responsibly, according to applicable planning and regulations, as well as involving the community in the planning process, implementation and supervision. Socialization encourages the community to actively participate in planning, implementing and supervising Village activities, such as participating in MusrenbangdesDes and supervising and implementing the Village APBD. Increasing awareness of the community and Village government is important for the community to participate in development. This activity is attended by several Village communities together with Village officials/government. Through socialization activities, it is hoped that in the future the community will participate in Village development or also in decision making, creating a good environment so that in the future the community and Village government can work to build the Village for the better.